Learning Techniques for Automatic Test Pattern Generation using Boolean Satisfiability - Liu Xin (Institute of Advanced Engineering and Science, 2013)
Automatic Test Pattern Generation (ATPG) is one of the core problems in testing of digital circuits. ATPG algorithms based on Boolean Satisfiability (SAT) turned out to be very powerful, due to great advances in the performance of satisfiability solvers for propositional logic in the last two decades. SAT-based ATPG clearly outperforms classical approaches especially for hard-to-detect faults. But its inaccessibility of structural information and don’t care, there exists the over-specification problem of input patterns. In this paper we present techniques to delve into an additional layer to make use of structural properties of the circuit and value justification relations to a generic SAT algorithm. It joins binary decision graphs (BDD) and SAT techniques to improve the efficiency of ATPG. It makes a study of inexpensive reconvergent fanout analysis of circuit to gather information on the local signal correlation by using BDD learning, then uses the above learned information to restrict and focus the overall search space of SAT-based ATPG. The learning technique is effective and lightweight. Experimental results show the effectiveness of the approach. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2861